SALDO: examples - Språkbanken Text (University of Gothenburg, 2024)
Example sentences for senses in SALDO

Exempelmeningar för SALDO-betydelser
SALDO: exempel
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik